2008
DOI: 10.1016/j.physletb.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

S-matrix at spatial infinity

Abstract: We provide a new method to construct the S-matrix in quantum field theory. This method implements crossing symmetry manifestly by erasing the a priori distinction between in- and out-states. It allows the description of processes where the interaction weakens with distance in space, but remains strong in the center at all times. It should also be applicable to certain spacetimes where the conventional method fails due to lack of temporal asymptotic states.Comment: 4 pages, LaTeX + revtex4; v2: normalization fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(85 citation statements)
references
References 4 publications
4
81
0
Order By: Relevance
“…We have thus shown that this is also true quantum mechanically. Note that this is analogous to what happens in Klein-Gordon theory for hypercylinders in Minkowski space [11][12][13].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…We have thus shown that this is also true quantum mechanically. Note that this is analogous to what happens in Klein-Gordon theory for hypercylinders in Minkowski space [11][12][13].…”
Section: Discussionsupporting
confidence: 55%
“…In [12,13] coherent states have been an essential tool for the computation of asymptotic amplitudes. This is equally the case in the present paper.…”
Section: Coherent Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…The starting point for this progress was the suggestion by Rovelli [8,9] of a procedure for computing the graviton propagator from Loop Quantum Gravity (LQG) [1,10,11] with the dynamics implemented covariantly in terms of a spin foam model. On the calculational side, the key ingredients are a boundary semiclassical spin network state peaked on large spins and an analytic expression for the large spin asymptotics of the spin foam vertex amplitude [12]; on the conceptual side, the framework is the boundary state formalism discussed in [1] and in [13,14,15,16,17], which prescribes how to compute observables in the boundary of a spacetime region with a path integral over the interior region only. IfÔ 1 ,Ô 2 are local boundary geometry observables (such as areas, dihedral angles, 3-volumes or lengths [18,19,20,21,22,23]) acting on a space of spin networks s , then the expectation value for their correlation in a boundary geometry q is given in the boundary state formalism by…”
Section: Introductionmentioning
confidence: 99%